EFFECT OF MAGNETIC FIELD ON MITES - Al Ani, Nabeel K (Al-Nahrain Journal of Science, 2010)
Two experiments were carried out to study the effects of magnetic field on two types of Mites.Broad Mite Polyphagotarsonemus latus (Banks) and two Spotted spider mites Tetranychus urticaeKoch. In the first experiment Tomato infected leaves were passed through500 gauss magnetic fieldfor different time intervals. In the second experiment the infected leaves were sprayed withmagnetic water (500 Gauss) for three repeated sprays. The results in both experiments revealed thatthe mite s number reduced as the experiment was carried out, however the eggs number wereincreased as the experiment was passed. This may be due to the effect of magnetic field on someenzymes inside the mites or the eggs which make them hyper active to lay down more eggs